CALCULATION OF THE BLADE AND THE BLADE-DISC COUPLING SYSTEM OF COMPRESSOR - YIN ZhiPeng; LI QuanTong; GAO XingWei; CHEN PengFei; TANG Ling (Jixie qiangdu)
A type of aero engine compressor blade model was built based on finite element. Dynamics of the clamped constrained blade was obtained by modal simulation and the influence of centrifugal force on the vibration of blades was researched. And then,the modal test was carried out to validate the model and the simulation data. Vibration analysis of blade disc finite element model was carried out based on cyclic symmetry method. The vibration mode and frequency of the coupling system with different working speeds were obtained. The result shows that the natural frequency of the coupling system is lower in the same order when compared with a single fixed blade. The resonance frequency and the corresponding rotor speed could be obtained by analysis of Campbell contours. It provides reference for the fault diagnosis,reliability analysis and life estimation.